An Analysis of Speech Acts Performed in Doobydobap Youtube Channel - Moza Yusiana (Edu-Ling: Journal of English Education and Linguistics, 2025)
Studying the linguistic strategies used by YouTubers is particularly valuable as it can indicate their strategies to engage with their audience and give insight into the mechanisms behind their success in attracting their audience. This study is conducted to analyze (1) the types of speech acts and (2) the audience responses reflect their engagement with the speech acts performed in Doobydobap YouTube channel using the theory of speech act proposed by Weigand (2017). The data of this study consist of two videos derived from the Doobydobap YouTube channel. The method used in this study is descriptive qualitative method. The results of this study reveals that there are all four types of speech acts identified from the data. There are 84,85% of the representatives speech acts, 10,61% of the directives speech acts, 2,65% of the declaratives speech acts, and 1,89% of the exploratives speech acts. The result of analysis also reveals that representatives type of speech act is the dominant speech act performed in Doobydobap YouTube channel. The effective use of all four types of the speech acts has played an important role in the success of the Doobydobap YouTube channel.